The Role of Sildenafil in Treating Brain Injuries in Adults and Neonates - Xiong, Ying; Wintermark, Pia (Frontiers in Cellular Neuroscience, 2022)
Sildenafil is a recognized treatment for patients suffering from erectile dysfunction and pulmonary hypertension. However, new evidence suggests that it may have a neuroprotective and a neurorestorative role in the central nervous system of both adults and neonates. Phosphodiesterase type 5 — the target of sildenafil — is distributed in many cells throughout the body, including neurons and glial cells. This study is a comprehensive review of the demonstrated effects of sildenafil on the brain with respect to its function, extent of injury, neurons, neuroinflammation, myelination and cerebral vessels.